English Education Students’ Perception of The Online Learning Process And Its Relationship Toward Their Reading Comprehension Achievement at Indo Global Mandiri University - Intan Kurniati Zahroq; Dio Resta Permana; Nike Angraini (Journal on Education, 2023)
The COVID-19 pandemic has changed the learning system at Indo Global Mandiri University from offline to online learning. Online learning is a type of education that is provided electronically via the internet or other computer-based technologies. It is also known as e-learning, remote education, or virtual learning. Due to the COVID-19 pandemic, colleges have conducted online learning during the previous three years. This study aimed to investigate the students' perceptions of online learning and the relationship between the students' perceptions of online learning and their reading comprehension achievement among English education students at Indo Global Mandiri University. The quantitative method used in this research was a correlational design to analyze the data. The population for this study were 121 English Language Education students. The data collection was done through a questionnaire of perception and reading comprehension test. This study showed that the perception of students was in the low category with a percentage of 38%, which means that the perception of English Education students at Indo Global Mandiri University was negative. While the results of the reading test of English education students were included in the advanced category with a percentage of 50%. It indicated that students' reading achievement was not much influenced by their perception of online learning.